Effect of tannic acid irrigation on microhardness of root canal dentin and bond strength of epoxy resin based sealer - Sevinc Askerbeyli Örs; Hacer Aksel; Selen Küçükkaya Eren; Dilara Zeybek (Selcuk Dental Journal)
Background:To investigate the effects of final irrigation protocols with tannic acid (TA) on dentin microhardness and push-out bond strength of an epoxy resin based sealer to root canal dentin.Methods: The 50 root halves were embedded in an acrylic resin for the microhardness measurement. After the initial baseline microhardness measurement, the root halves were randomly divided into 5 groups according to the final irrigation protocol used (n=10): distilled water (control), 10% TA for 2 min, 10% TA for 5 min, 20% TA for 2 min, and 20% TA for 5 min. After surface treatment, dentin microhardness values were recorded at close proximity to the initial indentation areas.